Targeted expression of mutated ALK induces neuroblastoma in transgenic mice - Heukamp, Lukas C.; Thor, Theresa; Schramm, Alexander; De Preter, Katleen; Kumps, Candy; De Wilde, Bram; Odersky, Andrea; Peifer, Martin; Lindner, Sven; Spruessel, Annika; Pattyn, Filip; Mestdagh, Pieter; et al. (Science Translational Medicine, 2012)
Activating anaplastic lymphoma kinase (ALK) mutations were recently detected in most familial and 10% of sporadic neuroblastomas. However, the role of mutated ALK in tumorigenesis remains elusive. We demonstrate that targeted expression of the most frequent and aggressive variant, ALK F1174L, is tumorigenic in mice. Tumors resembled human neuroblastomas in morphology, metastasis pattern, gene expression, and the presence of neurosecretory vesicles as well as synaptic structures. This ALK-driven neuroblastoma mouse model precisely recapitulated the genetic spectrum of the disease. Chromosomal aberrations were syntenic to those in human neuroblastoma, including 17q gain and MYCN oncogene amplification. Targeted ALK F1174L and MYCN coexpression revealed a strong synergism in inducing neuroblastoma with minimal chromosomal aberrations, suggesting that fewer secondary hits are required for tumor induction if both oncoproteins are targeted. Treatment of ALK F1174L transgenic mice with the ALK inhibitor TAE-684 induced complete tumor regression, indicating that tumor cells were addicted to ALK F1174L activity. We conclude that an activating mutation within the ALK kinase domain is sufficient to induce neuroblastoma development, and ALK inhibitors show promise for treating human neuroblastomas harboring ALK mutations.
CRIS-Team Scopus Importer:2023-03-21